Long-range ordering of two-dimensional wide bandgap tantalum oxide nanosheets in printed films. Issue 17 (15th April 2021) - Timmerman, Melvin A.; Xia, Rui; Wang, Yang; Sotthewes, Kai; Huijben, Mark; ten Elshof, Johan E.
Abstract : The exfoliation mechanism of high charge density 2D tantalum oxide nanosheets was optimized. Single monolayers and thicker thin films were realized and the bandgap of single nanosheets was measured electrically. Abstract : Two-dimensional oxide materials are a well-studied, interesting class of materials, enabled by the fact that their bulk layered metal oxides, such as titanates and niobates, can be easily exfoliated within minutes into 2D nanosheets. However, some promising oxide materials, such tantalum oxide, are much more difficult to delaminate, taking several weeks, due to the higher charge density resulting in stronger Coulombic interactions between the layers. This intrinsic constraint has limited detailed studies for exploiting the promising properties of tantalum oxide 2D nanosheets towards enhanced catalysis and energy storage. Here, we have studied in detail the exfoliation mechanism of high charge density 2D materials, specifically tantalum oxide (TaO3 ) nanosheets. Optimization of tetrabutylphosphonium hydroxide (TBPOH) as the exfoliation agent in a 2 : 1 ratio to HTaO3 has resulted in a dramatic reduction of the exfoliation time down to only 36 hours at 80 °C. Furthermore, single monolayers of TaO3 nanosheets with >95% coverage have been achieved by Langmuir–Blodgett deposition, while thicker layers (ranging from several tens of nanometers up to microns) exhibiting long-range ordering of the present nanosheets have been realized through inkjet printing. Interestingly, scanning tunneling microscopy analysis indicated a wide bandgap of ∼5 eV for the single TaO3 nanosheets. This value is significantly higher than the reported values between 3.5 and 4.3 eV for the layered RbTaO3 parent compound, and opens up new opportunities for 2D oxide materials.